"Being a Teacher": Emotions and Optimal Experience While Teaching Gifted Children. (March 2014) - Coleman, Laurence J.
The emotions experienced by teachers while teaching is a relatively unexplored avenue of research. One teacher, Alex, was studied using phenomenological interviews and participant observation to understand the emotions he experienced while teaching in a special program for gifted and talented children. Data were analyzed using inductive procedures. Alex experienced a variety of emotions generated when the instructional dynamics of the lesson were congruent or incongruent with his professional practical knowledge. Most of his emotions were positive. A compelling emotional state, "being a teacher, " was found to incorporate many of his feelings and was found repeatedly in his classes. Alex seemed to be trying to recreate being a teacher as he taught. His emotional state was interpreted to be isomorphic to what Csikszentmihalyi (1990) calls "optimal experience." The findings suggest that the special class setting established conditions which increased the probability that Alex would be having an optimal experience.